You signed in with another tab or window. Reload to refresh your session.You signed out in another tab or window. Reload to refresh your session.You switched accounts on another tab or window. Reload to refresh your session.Dismiss alert
I have been studying functional JS from mostly-adequate-guide while always looking here and at fantasy-land to understand the implementation.
After some confusion looking at Apply's signature, I discovered that fantasy-land inverted ap's argument order here.
from:
ap :: f (a -> b) -> f a -> fb
to:
ap :: f a -> f (a -> b) -> f b
However, looking the code here I see that the implementation follows the old signature. Although the new inverted order is opposite of haskell and looks ugly imo, I guess we should follow fantasy-land's specification.
The text was updated successfully, but these errors were encountered:
Hi,
I have been studying functional JS from mostly-adequate-guide while always looking here and at fantasy-land to understand the implementation.
After some confusion looking at Apply's signature, I discovered that fantasy-land inverted
ap
's argument order here.from:
ap :: f (a -> b) -> f a -> fb
to:
ap :: f a -> f (a -> b) -> f b
However, looking the code here I see that the implementation follows the old signature. Although the new inverted order is opposite of haskell and looks ugly imo, I guess we should follow fantasy-land's specification.
The text was updated successfully, but these errors were encountered: